One-dimensional data analysis for aquifer layer in Pancuma Village, Tojo Una-Una, Central Sulawesi. Issue 1 (January 2021) - Sastrawan, F D; Wulandari, R; Rusli, M; Rahmania,; Arisalwadi, M
Abstract: The need for water resources continues to increase from year to year to meet various needs. The availability of water resources is increasingly limited due to seawater intrusion or water pollution. Pancuma Village is one of the coastal areas where it is necessary to study the potential of groundwater, especially during the dry season. One way to determine the presence of the groundwater aquifer layer is by using the resistivity method. This method is an effective geophysical method for shallow exploration so that it can be used to determine the structure beneath the earth's surface. The configuration used in this study is the Schlumberger configuration. Research in Pancuma Village aims to determine the subsurface stratigraphy of the study area based on the resistivity value and to determine the distribution of groundwater aquifers in the study area. The results obtained from this study are that there are four types of subsurface layers in the study area, namely topsoil, claystone, iron sand, and alternating sandstone with conglomerates which are the aquifer layer in the study area. The resistivity value estimated at the aquifer layer ranges from 119 Ωm - 529 Ωm with a thickness of up to 45 meters.